Studi Deskriptif Permasalahan Status Gizi Pada Anak Usia 6-24 Bulan Di Kota Manado - Endang Puji Ati; Rakhmawati Agustina (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
The toddler period is a golden period that determines the rate of growth and development of toddlers both physically, mentally and emotionally. Assessment of nutritional status Assessment of nutritional status of toddlers using standard and measurable parameters can be used as a monitoring item for nutritional problems in toddlers. This study aims to describe the findings based on research data conducted in 2021 on 96 toddlers in the working area of the Ranomuut Public Health Center, Manado City, North Sulawesi Province. Primary anthropometric and age data were collected on toddlers 6-24 months and obtained data that 26% of toddlers have nutritional status in the poor category (<2SD) and 74% of them have nutritional status in the good category (? -2 SD to +2SD). Even though there is no urgency found in the results of this study, the conclusions of the research need to be published, and it is hoped that this can be used as a reference for future research.